Impact response of thin-walled tubes: A prospective review - Fauziah, Mat; Khairul Azwan, Ismail, Dr.; Sazali, Yaacob, Prof. Dr.; Inayatullah, Othman (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/